Wolves and Dogs May Rely on Non-numerical Cues in Quantity Discrimination Tasks When Given the Choice - Rivas-Blanco, Dániel; Pohl, Ina-Maria; Dale, Rachel; Heberlein, Marianne Theres Elisabeth; Range, Friederike (Frontiers in Psychology, 2020)
A wide array of species throughout the animal kingdom has shown the ability to distinguish between quantities. Aside from being important for optimal foraging decisions, this ability seems to also be of great relevance in group-living animals as it allows them to inform their decisions regarding engagement in between-group conflicts based on the size of competing groups. However, it is often unclear whether these animals rely on numerical information alone to make these decisions or whether they employ other cues that may covary with the differences in quantity. In this study we used a touch screen paradigm to investigate the quantity discrimination abilities of two closely related group-living species, wolves and dogs, using a simultaneous visual presentation paradigm. Both species were able to successfully distinguish between stimuli of different quantities up to 32 items and ratios up to 0.80, and their results were in accordance with Weber's law (which predicts worse performances at higher ratios). However, our controls showed that both wolves and dogs may have used continuous, non-numerical cues, such as size and shape of the stimuli, in conjunction with the numerical information to solve this task. In line with this possibility, dogs' performance greatly exceeded that which they had shown in other numerical competence paradigms. We discuss the implications these results may have on these species' underlying biases and numerical capabilities, as well as how our paradigm may have affected the animals' ability to solve the task.